Temporal and spatial distribution of plankton community in three Indonesian salt pond environments (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Susilowati R, Bengen DG, Krisanti M, Januar HI, Rusmana I. 2023. Temporal and spatial distribution of plankton community in three Indonesian salt pond environments. Biodiversitas 24: 1833-1844. Plankton is a biological community that plays an important role in biological systems during salt crystallization. The correlation between plankton communities and water quality parameters was examined in three salt pond center areas (Brebes, Tuban, and Sampang). The values of nutrient content in Brebes were higher compared to other locations, with phosphate (5.38-5.66 mg/L), nitrate (0.17-0.74 mg/L), nitrite (0.07-0.1 mg/L), and total organic matter (0.03-0.07 mg/L). Based on multivariate analysis, there was no significant difference in the abundance of plankton among the three salt pond locations. Furthermore, Spearman's correlation test indicated a negative correlation (Sig
Keywords: Phytoplankton, salt ponds, water quality, zooplankton